Scientific Criminal Investigation Legal Studies in the Police Investigation Process - ., Sumali; Bhirini Slamet, Aprilia; Monique, Cindy (KnE Social Sciences, 2022)
Scientific Criminal Investigation can be a method in the investigation process carried out by investigators to prove evidence in proving criminal cases. Process of the Scientific Criminal Investigation method in proving it can minimize errors with fast, precise, and accurate examinations. The investigation process of scientific evidence by investigators also needs to be supported by technical assistance from several branches of forensic science. This study aims to obtain a description of the method of Scientific Criminal Investigation in the disclosure of criminal acts using quantitative methods. The application of the Scientific Criminal Investigation Method in the evidentiary process has a role in uncovering evidence and evidence in criminal cases following the Criminal Procedure Code, namely through letter evidence, instructions, and expert statements. Thus, proving a case using the Scientific Criminal Investigation method is a breakthrough in the evidentiary process of proving a criminal case. In this way, the Scientific Criminal Investigation Method becomes a reference for investigators in the process of proving criminal cases because scientific crime studies are also supported by increasing and sophisticated sciences, including the special tools created. Keywords: scientific criminal investigation, investigation, evidence